2013
DOI: 10.1002/cplu.201300075
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Peroxidase Catalytic Activity of Fe7S8 Nanowires Templated from [Fe16S20]/Diethylenetriamine Hybrid Nanowires

Abstract: Iron sulfide compounds are emerging as an important family of functional materials owing to their important properties and their applications in different technical fields. Well‐defined Fe7S8 nanowires templated by thermal decomposition of [Fe16S20]/diethylenetriamine hybrid nanowires under an argon atmosphere are reported. As‐prepared Fe7S8 nanowires show typical Michaelis–Menten kinetics and good affinity to both H2O2 and 3,3′,5,5′‐tetramethylbenzidine. At pH 7.0, the constructed UV/Vis sensor showed a linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Since Yan group first found that magnetic nanoparticles exhibit peroxidase simulation properties, the reports on enzyme mimetic properties of metal nanomaterials become more and more attractive . For example, iron-based materials (Fe 3 O 4 , Fe 2 O 3 , FeS, and Fe 7 S 8 ), manganese-based materials (MnO 2 and Mn 3 O 4 ), , cobalt-based materials (Co 3 O 4 , CoS, and Co 9 S 8 ), copper-based materials (CuO, Cu 2 O, and CuS), vanadium-based materials (VO 2 , V 2 O 3 , and V 2 O 5 ), etc. have been reported to exhibit enzyme mimetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Since Yan group first found that magnetic nanoparticles exhibit peroxidase simulation properties, the reports on enzyme mimetic properties of metal nanomaterials become more and more attractive . For example, iron-based materials (Fe 3 O 4 , Fe 2 O 3 , FeS, and Fe 7 S 8 ), manganese-based materials (MnO 2 and Mn 3 O 4 ), , cobalt-based materials (Co 3 O 4 , CoS, and Co 9 S 8 ), copper-based materials (CuO, Cu 2 O, and CuS), vanadium-based materials (VO 2 , V 2 O 3 , and V 2 O 5 ), etc. have been reported to exhibit enzyme mimetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The previous report of WS 2 nanosheets having peroxidase activity also displayed maximum activity at pH 4.0 . Yao et al in their work showed that iron sulfide nanowires had the potential as a peroxidase mimetic having maximum activity at a pH value of 4.0 . Vanadium oxide-mesoporous carbon composite showed peroxidase activity for detection of glucose.…”
Section: Resultsmentioning
confidence: 91%
“…1h, the powder X-ray diffraction (PXRD) pattern shows that the emergence of diffraction peaks is similar to the reported FeS-amine precursors. 60,61 Fourier transform infrared (FTIR) spectra (Fig. 1g, cyan line) and energy-dispersive X-ray spectroscopy (EDS) analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…FeS-DETA was synthesized using a modified method reported by Yu's group. 60,61 In a typical synthesis procedure, FeSO 4 Ĵ7H 2 O (0.2780 g), C 2 H 5 NS (0.1526 g), H 2 O (8 mL) and diethylenetriamine (DETA, 8 mL) were added to a Teflonlined autoclave with a capacity of 20 mL. The mixture was stirred for 20 min to form a homogeneous suspension.…”
Section: Synthesis Of Inorganic-organic Hybrid Fes-deta Nanosheetsmentioning
confidence: 99%